GE_GERICHTE P/14816/2011 vom 27. März 2012 - GE Cour de justice (2012)
; SECRET PROFESSIONNEL ; MOYEN DE PREUVE ; CONSULTATION DU DOSSIER ; POLICE ; MÉDIA ; DIFFAMATION ; BONNE FOI SUBJECTIVE | CPP.310; CPP.309; CPP.102; CPP.436; CP.320; CP.73